The Intentional Stance Test-2: How to Measure the Tendency to Adopt Intentional Stance Towards Robots - Spatola, Nicolas; Marchesi, Serena; Wykowska, Agnieszka (Frontiers in Robotics and AI, 2021)
In human-robot interactions, people tend to attribute them mental states such as intentionality to make sense of their behaviour: the intentional stance. These inferences deeply influence how one will consider, engage and behave towards robots. However, people highly differ in their likelihood to adopt this intentional stance. Therefore it seems crucial to assess these interindividual differences to better evaluate and understand human-robot interactions. In two studies we developed and validated the structure of a task aiming at evaluating to what extent people adopt the intentional stance toward robots. The method consists in a task that probes participants’ stance by requiring them to choose the likelihood of an explanation (mentalistic vs. mechanistic) of behaviour of a robot depicted in a naturalistic scenario. Results showed a reliable psychometric structure of the present task to evaluate the mentalistic bias of participants as a proxy of the intentional stance. We further discuss the importance of considering these interindividual differences in human-robot interactions studies and social robotics.